Great Idea, but how do I do it? A practical example of learning object creation using SGML/XML - Janet Bartz (The Canadian Network for Innovation in Education (CNIE), 2002)
The educational community is interested in learning objects, what they are, how they are used, and the many benefits derived from their use. Most educators are familiar with the value of learning objects in theory, but on the practical side are wondering what is involved in creating them. This paper offers a "how-to" of learning object implementation, for text, based on four years experience working with Open Learning Agency's structured content development model. Throughout the paper the analogy of a yogurt container will be used to help illustrate the concepts behind implementing a structured content development model.